2005
DOI: 10.1214/105051605000000601
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling control for queueing systems with many servers: Asymptotic optimality in heavy traffic

Abstract: A multiclass queueing system is considered, with heterogeneous service stations, each consisting of many servers with identical capabilities. An optimal control problem is formulated, where the control corresponds to scheduling and routing, and the cost is a cumulative discounted functional of the system's state. We examine two versions of the problem: "nonpreemptive," where service is uninterruptible, and "preemptive," where service to a customer can be interrupted and then resumed, possibly at a different st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
172
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(175 citation statements)
references
References 13 publications
1
172
0
2
Order By: Relevance
“…Atar et al [6] proved that the policies obtained from this approach are asymptotically optimal. Atar [4,5] followed a similar approach to that in [6] to find asymptotically optimal policies for tree-like systems. In Mandelbaum et al [33], they used a uniform acceleration technique to obtain the fluid and diffusion limit of a Markovian service network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Atar et al [6] proved that the policies obtained from this approach are asymptotically optimal. Atar [4,5] followed a similar approach to that in [6] to find asymptotically optimal policies for tree-like systems. In Mandelbaum et al [33], they used a uniform acceleration technique to obtain the fluid and diffusion limit of a Markovian service network.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our initial investigation suggests that the insights gained from studying the V-model are useful in analyzing more complicated network structures (Gurvich 2004). Other researchers have also tackled this general skill-based routing (SBR) problem (e.g., Bassamboo et al 2006aBassamboo et al , 2006bAtar 2005;Tezcan and Dai 2007;Gurvich and Whitt 2006), but many issues remain unresolved.…”
Section: Directions For Future Researchmentioning
confidence: 99%
“…Papers [24] and [7] formulated a diffusion control problem to study a V-parallel server system with impatient customers in many-server heavy traffic; [7] proved that the policies obtained from this approach are asymptotically optimal. Works [5,6] followed a similar approach to that in [7] to find asymptotically optimal policies for tree-like systems. In [38] and [15] it is shown that a greedy policy is asymptotically optimal first for N-systems and then for general systems when the service rates are only server pool dependent.…”
Section: Review Of Related Previous Workmentioning
confidence: 99%
“…To improve exposition, from this point on in the proof, consider a special system with I = {1, 2, 3, 4}, J = {5, 6, 7, 8}, and basic activities E b = {(1, 5), (2,5), (2,6), (2,7), (3,7), (3,8), (4,5)}, see Fig. 1.…”
Section: Proof Of Theorem 31mentioning
confidence: 99%
See 1 more Smart Citation